Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/w12010014
|View full text |Cite
|
Sign up to set email alerts
|

Column Experiments on Sorption Coefficients and Biodegradation Rates of Selected Pharmaceuticals in Three Aquifer Sediments

Abstract: The presence of pharmaceuticals in the environment, and in groundwater, has been recognized as a great environmental concern. Biodegradation and sorption are the main processes leading to the removal of contamination from the water phase. The aim of this study was to determine the transport processes of selected pharmaceuticals (antipyrine, atenolol, carbamazepine, caffeine, diclofenac, ketoprofen, sulfamethoxazole) in selected sediments (coarse sand, medium sand, sandy loam) in laboratory experiments. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…The modeled and simulated mass fluxes fitted well after adjustment with a K d value of 3.0 mL·g −1 , rather than using the experimental Kd=7.7±0.2mL·normalg1(Figure 4a), (|ΔΦtrue¯|=|trueΦOΦM¯|=0.01mg·normalh1 and σΔΦ=0.54mg·normalh1) (Figures 4b and 4c). This observation is consistent with a previous study reporting a sorption coefficient twice lower for the pharmaceutical atenolol in column experiments than in batch sorption experiments (Kiecak et al., 2019). Although in‐bed measurements were not possible for experiments with FB291, similar observed and simulated patterns of FB291 penetration into the sediment bed confirmed the validity of simulations in the case of IHF FB291 (Figure 6a and 6b).…”
Section: Model Validation Versus Experimentssupporting
confidence: 94%
“…The modeled and simulated mass fluxes fitted well after adjustment with a K d value of 3.0 mL·g −1 , rather than using the experimental Kd=7.7±0.2mL·normalg1(Figure 4a), (|ΔΦtrue¯|=|trueΦOΦM¯|=0.01mg·normalh1 and σΔΦ=0.54mg·normalh1) (Figures 4b and 4c). This observation is consistent with a previous study reporting a sorption coefficient twice lower for the pharmaceutical atenolol in column experiments than in batch sorption experiments (Kiecak et al., 2019). Although in‐bed measurements were not possible for experiments with FB291, similar observed and simulated patterns of FB291 penetration into the sediment bed confirmed the validity of simulations in the case of IHF FB291 (Figure 6a and 6b).…”
Section: Model Validation Versus Experimentssupporting
confidence: 94%
“…In long-term (180 days) degradation experiments, using low atrazine concentrations of 20 µg L −1 in water circulating columns at a flow rate of 2 mL min −1 , atrazine dissipation rates have been estimated to be two to five times faster than in stagnant flasks [5], while pharmaceuticals dissipation was not enhanced at flow rates of 1.7-3.4 mL min −1 [65]. The short-term results of this study showed that at quite a high atrazine concentration below 10-18 mg L −1 , high flow rate (16.7 mL min −1 )-induced changes in the sediment columns did not improve atrazine dissipation, apparently due to the good colloid formation ability [21][22][23], while the amount adsorbed to the sediments was low (about 50.1 µg).…”
Section: Atrazine-contaminated Aquifer Sediments and Remediationmentioning
confidence: 99%
“…Column experiments coupled with numerical modelling are useful tools to rapidly test soil amendments prior to its incorporation in real VFs and to delineate the dynamics of water flow and contaminant transport within porous media providing predictive insights into the fate and migration of contaminants. The predominant focus in pharmaceuticals of recent research has leaned towards experiments conducted under saturated conditions particularly to forecast their transport in aquifers and natural soils, as well as during processes such as aquifer recharge, agriculture and urban irrigation and soil aquifer treatment [41][42][43][44][45][46][47]. In contrast, investigations carried out under unsaturated conditions are comparatively limited, and even scarcer are studies conducted under unsaturated conditions that employ soil amendments as a treatment approach for pharmaceutical removal.…”
Section: Introductionmentioning
confidence: 99%